2018
DOI: 10.3390/met8100850
|View full text |Cite
|
Sign up to set email alerts
|

Machining Performance of TiAlN-Coated Cemented Carbide Tools with Chip Groove in Machining Titanium Alloy Ti-6Al-0.6Cr-0.4Fe-0.4Si-0.01B

Abstract: In this paper, TiAlN-coated cemented carbide tools with chip groove were used to machine titanium alloy Ti-6Al-0.6Cr-0.4Fe-0.4Si-0.01B under dry conditions in order to investigate the machining performance of this cutting tool. Wear mechanisms of TiAlN-coated cemented carbide tools with chip groove were studied and compared to the uncoated cemented carbide tools (K20) with a scanning electron microscope (SEM) and energy dispersive spectrometer (EDS). The effects of the cutting parameters (cutting speed, feed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Da Silva et al [ 6 ] showed that adhesion and attrition are dominant wear mechanisms in the machining of a Ti–6Al–4V alloy with PCD (Polycrystalline Diamond) tools with a high pressure coolant. Similar conclusions can be drawn from research conveyed by Ren et al [ 8 ] regarding machining with TiAlN-coated cemented carbide tools with chip groove. In turn, tool life improvement can be obtained from machining with cooling fluids.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Da Silva et al [ 6 ] showed that adhesion and attrition are dominant wear mechanisms in the machining of a Ti–6Al–4V alloy with PCD (Polycrystalline Diamond) tools with a high pressure coolant. Similar conclusions can be drawn from research conveyed by Ren et al [ 8 ] regarding machining with TiAlN-coated cemented carbide tools with chip groove. In turn, tool life improvement can be obtained from machining with cooling fluids.…”
Section: Introductionsupporting
confidence: 87%
“…During machining, the main problems are high temperature and concentration of stresses on the cutting edge, which causes the accelerated tool wear [ 6 , 7 , 8 ]. This is partly due to the poor thermal conductivity of titanium alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors associated with the cutting tool can also affect the chip forming and breaking process. For example, the authors of [39] and Ren et al [40] presented the results of tests that concerned the impact of chip breaker geometry or protective coating on the cutting insert rake face. In turn, Pusavec et al [41] and Yi et al [42] discussed issues related to the optimization of machining of difficult-to-cut materials on CNC machine tools, due to carbon emissions.…”
Section: Chip Breakability Descriptionmentioning
confidence: 99%
“…In recent years, carbide composite tools have been highly sought after by the industry for their excellent cutting performance and widely used for machining titanium alloys [ 1 ], bearing steel [ 2 ] and other materials [ 3 , 4 ]. In contrast, carbide tools suffer from severe tool wear, short service life and poor machining quality when used for difficult-to-cut materials such as printed circuit boards and ceramic-based composites [ 5 ].…”
Section: Introductionmentioning
confidence: 99%